2019
DOI: 10.1101/865089
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prolonged inflammation leads to ongoing damage after spinal cord injury

Abstract: 27The pathogenesis of spinal cord injury (SCI) remains poorly understood and treatment remains 28 limited. Emerging evidence indicates the severity of post-SCI inflammation and an ongoing 29 controversy in the roles of astrocytes with studies identifying astrocytes as associated both with 30 ongoing inflammation and damage as well as potentially having a protective role. We have 31 completed an extensive systematic study with MRI, histopathology, proteomics and ELISA 32 analyses designed to further define the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…It has been reported that prolonged in ammation leads to ongoing damage after spinal cord injury. [12] In a comparison of the three groups, although the immediate decompression group showed the most rapid functional improvement, there was no signi cant difference between the subacute decompression group and the immediate decompression group by four weeks. Clinically, in patients with mild to moderate spinal cord injury, the results suggest that decompression itself may lead to improvement in motor function, regardless of the timing of decompression surgery.…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that prolonged in ammation leads to ongoing damage after spinal cord injury. [12] In a comparison of the three groups, although the immediate decompression group showed the most rapid functional improvement, there was no signi cant difference between the subacute decompression group and the immediate decompression group by four weeks. Clinically, in patients with mild to moderate spinal cord injury, the results suggest that decompression itself may lead to improvement in motor function, regardless of the timing of decompression surgery.…”
Section: Discussionmentioning
confidence: 88%
“…As we all know, it has been reported that the mechanism of SCI is very complex, including in ammation reaction, the less nurotrophic factors and neurons lost within the lesion site, which may inhibit axonal regrowth [29]. In ammation is one of the main mechanisms after the acute SCI [30,31]. Meanwhile, previous studies have revealed that caspase-1 appeared to play a role in tissue injury by participating in the in ammatory pathways [32].…”
Section: Discussionmentioning
confidence: 99%
“…Three main paths for evacuation of excess fluid from acute cerebral edema have been identified in animal models: (1) via the glia limitans externa to the subarachnoid space, (2) via the glia limitans interna and ependyma to the ventricles/central canal, and (3) via the BBB into the lumen of blood vessels ( 26 ). Fluid is also lost into the site of injury, which is converted into a “cavity of injury” ( 27 ). Recent research has confirmed that excess edema fluid leaves the brain through an integrated system of astrocytes which overexpress acquaporin-4 (AQP4) ( 28 30 ).…”
Section: Intracranial Hypertension (Hicp): How To Escalate Therapymentioning
confidence: 99%